A Comparative Analysis of Climate Change Magnitude and Direction in Europe from the Pliocene to the Anthropocene - Ivajnšič, Danijel; Donša, Daša (Journal for Geography, 2025)
Understanding paleo-climate changes on Earth is crucial for the development of global climate models that predict the climate of the 21st century, while these changes also serve as an important driver of recent biodiversity patterns. In this paper, we use Change Vector Analysis (CVA) to examine changes in average annual air temperature and precipitation in Europe, based on the PaleoClim and CHELSA databases, from the Pliocene to the end of the 21st century. We focus on regional similarities and differences in the magnitude and direction of changes. The results highlight the natural dynamics of the climate and serve as a calibration for future change forecasts, which form the basis for current and future adaptation strategies in Europe.